Konflik Batin Tokoh Utama pada Novel Pulang Karya Tere Liye dan Implementasinya Sebagai Bahan Ajar Sastra di SMA: Tinjauan Psikologi Sastra - Mistinurasih, Mistinurasih; , Pro.Dr.Ali Imron Al-Ma'ruf,M.Hum (2017)
Abstract The purpose of this study is to (1) describe the background sosio-historis novelist; (2) set out the structure novel Pulang creation Tere Liye; (3) reveals the inner conflict of the main character in the novel Pulang creation Tere Liye; (4) describes the implementation of the novel Pulang creation Tere Liye as one of the teaching material in high school literature. This study used descriptive qualitative method. Data in this study were sentences and excerpts of the novel Pulang creation Tere Liye. Source data in this study divided into two primary data sources and secondary data sources. The primary data source in this study is novel Pulang karya Tere Liye and secondary data sources on this research is a biography of a novelist. The data is validated by using triangulation theory. Data analyis technique used is the method of reading semiotic models. The results of this study are (1) background sosio-historis Tere Liye; (2) structures that were examined in research consisted of themes and facts of the story. There are main characters and simple figures. Groove in the story is a mix of groove. A background can be divided into backlight, baclight time, and social background. The theme of the novel is a man who struggles to maintain fame of Tong Family; (3) the inner conflict of the main character in the novel; (4) implementation as teaching material in high school literature II semester of class XII with basic competencies 3.1 and core competencies 4.1 Keywords: Inner Conflict, Novel Pulang creation Tere Liye, Structure Novel.